Family Coping Mechanisms in Response to Stunting Events in Toddlers in the Working Area of Pekanheran Health Center - Rosy, Alice; Elmukhsinur, Elmukhsinur; Rusherina, Rusherina (JURNAL PROTEKSI KESEHATAN, 2025)
Stunting remains a public health issue in Indonesia, with an estimated 27.7% of children under five years old experiencing stunting. The role of parents and family is very important in meeting the needs of children and providing them with good growth and development, so that children can live well. A positive family coping approach is very important. Without effective family coping mechanisms, the family's functions cannot be adequately achieved. Desa Air Jernih is a Stunting Locus Village in 2024. The purpose of this study is to determine the relationship between family coping mechanisms and the incidence of stunting in toddlers, using a total population technique involving 89 families with toddlers and employing three types of questionnaires: a respondent characteristic questionnaire, a toddler height measurement, and a parental coping mechanism questionnaire using the F-COPES instrument. Based on statistical testing using the chi-square method, a p-value of 0.282 was obtained, indicating that there is no relationship between family coping mechanisms and the incidence of stunting.